ANALISIS PENGARUH ALOKASI DANA DESA, BELANJA DESA, DAN PEMBERDAYAAN MASYARAKAT TERHADAP KESEJAHTERAAN MASYARAKAT DESA DI KECAMATAN SAWIT KABUPATEN BOYOLALI - Cindy Aulia Febriyanti; Suprihati Suprihati; Yuwita Ariessa Pravasanti (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the influence of Village Fund Allocation, Village Expenditure, and Community Empowerment on Community Welfare in Sawit District, Boyolali Regency. This research employed a quantitative approach using primary data obtained through questionnaires distributed to village officials in 12 villages located in Sawit District. The population consisted of 104 respondents and the sampling technique used was saturated sampling. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis using SPSS software. The results indicate that Village Fund Allocation, Village Expenditure, and Community Empowerment have positive and significant effects on Community Welfare. Effective management of village funds, appropriate village expenditures, and successful community empowerment programs contribute significantly to improving the quality of life and welfare of rural communities. Therefore, village governments are expected to enhance transparency, accountability, and effectiveness in managing village finances while strengthening community empowerment programs to achieve sustainable rural development. The findings of this study provide practical implications for village governments in formulating policies related to village fund management, village expenditures, and community empowerment programs to improve community welfare sustainably.